The situation awareness of health workers about needlestick and sharp injuries at hospital (Bangladesh Journal of Medical Science, 2021)
Background: The nosocomial infection occurs in patients who are under medical treatments in hospitals or other health facilities, which has not yet occurred at the time of admission. This infection can occur as delivering treatments for other diseases; and even after the patients has returned from the hospital.The purpose of this study is to analyze the effectiveness of an education about the danger of needlestick to the situational awareness of health workers regarding the needlestick and sharp injuries in hospitals.Method: This study is a quasi-experiments with pretest and post-test control group design. The samples of this study was collected using purposive sampling with 98 respondents in the experiment group and 29 respondents in the control group. The data were analyzed by Wilcoxon and Independent sample T test. Meanwhile, the data were collected by questionnaires.Result: The measurement results of the situation awarenessin the control group, mean is 45.31, and SD is 3.57; in the treatment group, mean is 46.77, and SD is 4.04.The differences of the situation awareness of needlestick and sharp objects in the control group, before and after education, is p = 0.981 (> 0.05); the result is not significant. The differences of the situation awareness of needlestick and sharp objects in the treatment group, before and after education, is p = 0.001 (